High-performance ultrathin rare earth permanent magnet sheet and preparation method thereof
By melting iron raw materials and samarium raw materials under vacuum conditions, forming samarium ferroalloy sheets, and homogenizing, hydrogenating and nitriding treatments, high-performance Sm2Fe17Nx magnetic powder is obtained, which solves the problems of low magnetic properties and poor corrosion resistance of samarium ferro nitrogen permanent magnet sheets in the prior art, and realizes the preparation of high-performance rare earth permanent magnet sheets with a thickness of less than 0.4mm, meeting the needs of specific application scenarios.
Patent Information
- Application Number
- CN202510206958.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-25
AI Technical Summary
It is difficult to prepare high-performance samarium iron nitrogen permanent magnet sheets with thickness less than 0.4mm, and the magnetic sheets have low magnetic properties and poor corrosion resistance, which cannot meet the needs of certain application scenarios.
By melting the iron raw material and the samarium raw material under vacuum, forming a samarium ferroalloy sheet, and homogenizing, hydrogenating and nitriding treatments, high-performance Sm2Fe17Nx magnetic powder was obtained. Then phosphoric acid and corrosion inhibitor are added for ball milling surface treatment, and finally molded with a flat vulcanizer to prepare a high-performance rare earth permanent magnet sheet with a thickness of 0.2mm-0.4mm.
The high magnetic performance of the magnetic sheet is achieved, the surface magnet exceeds 500Gs, and has good corrosion resistance, which can meet the needs of specific application scenarios and reduce the preparation cost.
Smart Images

Figure CN119694774A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth permanent magnet material preparation, and in particular relates to a high-performance ultra-thin rare earth permanent magnet sheet and a preparation method thereof. Background Art
[0002] Rare earth permanent magnet materials are widely used in various fields due to their excellent magnetic properties. Among them, samarium iron nitrogen permanent magnet materials are regarded as a new generation of permanent magnet materials after neodymium iron boron due to their high Curie temperature, high coercive force and excellent anti-oxidation performance. However, since samarium iron nitrogen compounds are easily decomposed at high temperatures, they cannot be prepared by traditional sintering processes and can only be made into bonded magnets. In the prior art, samarium iron nitrogen magnetic powder is usually prepared by powder metallurgy process, and then mixed with organic binder and pressed into shape. However, since the magnetic properties of bonded magnets are relatively low and it is difficult to further process them after pressing and forming, its promotion in practical applications is limited.
[0003] The calendering process can produce thin SmFeN permanent magnet materials, but due to the high hardness of SmFeN magnetic powder, calendering processing has certain difficulties, especially when the calendering thickness is less than 0.4mm, the calender is difficult to process. At the same time, the surface magnetism of the thin magnets prepared by calendering is low, which cannot meet the needs of practical applications. Moreover, the magnets have poor corrosion resistance and are prone to rust, which cannot meet the needs of specific usage scenarios. Patent document CN118213147A discloses an ultra-thin flexible magnetic composite material and a preparation method thereof, which belongs to the technical field of rubber magnetic materials. The magnetic strip includes the following raw materials by weight: 5-10 parts of SmFeN magnetic powder, 90-95 parts of ferrite magnetic powder, 8-9 parts of binder, 0.5-1 parts of lubricant, 0.1-0.3 parts of thermal stabilizer, 0.5-0.6 parts of silane coupling agent, and 0.5-1.5 parts of ethanol. Ferrite is used as the main raw material, and after mixing with SmFeN rare earth magnetic powder, an ultra-thin flexible magnetic composite material is prepared by calendering process. Although the thickness of the flexible magnetic composite material prepared by this method reaches 0.3mm-0.9mm, there are still some application scenarios such as magnetic eyelashes that require the thickness of the magnetic sheet to be as thin as about 0.2mm, the surface magnetism is higher than 500Gs and corrosion resistance, and the existing technology is still difficult to meet the requirements. Therefore, it is urgent to develop a new type of samarium iron nitrogen permanent magnetic material and its preparation method to improve the magnetic properties of the material and solve the difficulties of calendering processing, so as to promote the practical application of samarium iron nitrogen permanent magnetic materials. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a high-performance ultra-thin rare earth permanent magnet sheet to solve the problems of severe magnetic loss, poor corrosion resistance and large thickness of the rare earth permanent magnet sheet during the preparation process. The second object of the present invention is to provide a rare earth permanent magnet sheet prepared by the method for preparing a high-performance ultra-thin rare earth permanent magnet sheet.
[0005] In a first aspect, a method for preparing a high-performance ultra-thin rare earth permanent magnet sheet comprises the following steps: S1, melting all the iron raw materials and 45wt%-55wt% of the samarium raw materials under vacuum conditions, adding the remaining samarium, continuing to smelt, and pouring the obtained molten alloy onto a cooling roller to obtain a samarium-iron alloy sheet; S2, sequentially performing homogenization treatment, hydrogenation treatment and nitridation treatment on the samarium-iron alloy sheet to obtain nitrided magnetic powder; S3, adding phosphoric acid and corrosion inhibitor to the magnetic powder, wet-milling and drying to obtain surface-treated magnetic powder; S4, adding a binder to the surface treated magnetic powder, and kneading to obtain magnetic particles; S5. The magnetic particles are pressed by a flat vulcanizing machine to obtain rare earth permanent magnet sheets.
[0006] As a further solution of the present invention, in S1, the samarium raw material and the iron raw material are weighed according to a molar ratio of 2:17, and 1wt%-10wt% of the samarium raw material is added; According to the chemical formula of samarium iron alloy Sm2Fe 17 , calculated with 2 mol Sm and 17 mol Fe, theoretically, it is necessary to weigh m(Sm)=2mol×150.36g / mol=300.72g, m(Fe)=17mol×55.86g / mol=949.45g; on this basis, Sm is additionally weighed (i.e., excess) by 1wt%-10wt%, which is converted into a mass of m(Sm)=300.72g+3.0072g-300.72g+30.072g=303.7272g-330.792g.
[0007] As a further embodiment of the present invention, in S1, all the iron raw materials and 50 wt% of the samarium raw materials are melted under vacuum conditions.
[0008] As a further solution of the present invention, in S1, the vacuum degree is less than 10 Pa, the melting temperature is 1510° C.-1580° C., and the melting time is 30 min-50 min.
[0009] As a further solution of the present invention, in S1, the molten alloy is poured onto the cooling roller through the tundish and the runner to form a continuous samarium-iron alloy strip, and falls onto the water-cooled plate below to obtain a samarium-iron alloy sheet.
[0010] As a further solution of the present invention, the rotation speed of the cooling roller is 1 r / min-3 r / min.
[0011] As a further solution of the present invention, in S2, the homogenization treatment is specifically to put the samarium iron alloy sheet into a heat treatment furnace, evacuate the furnace, and then heat treat it at a temperature of 900°C-1100°C for 7.5h-8.5h.
[0012] As a further solution of the present invention, the vacuum degree is 1×10 -2 Pa.
[0013] As a further solution of the present invention, in S2, the hydrogenation treatment is specifically to cool the samarium-iron alloy sheet after homogenization treatment to 250°C-300°C and keep it warm, and introduce hydrogen into the furnace under vacuum environment, the absolute pressure of hydrogen is controlled at 0.05MPa-0.15MPa, and the hydrogenation time is 2h.
[0014] As a further scheme of the present invention, in S2, the nitriding treatment is specifically to uniformly increase the temperature to 350°C-450°C at a rate of 10°C / min, fill with nitrogen to 0.5MPa, and keep the temperature for reaction for 1 hour; then uniformly increase the temperature to 500°C-550°C at a rate of 0.2°C / min, and keep the temperature for reaction for 10 hours; cool to room temperature (25°C-30°C) with the furnace to obtain the nitrided magnetic powder.
[0015] As a further solution of the present invention, in S2, the average particle size of the magnetic powder after nitridation is 20±2 μm.
[0016] As a further solution of the present invention, in S3, the amount of phosphoric acid added is 1wt% calculated based on the weight of the magnetic powder; The corrosion inhibitor is benzotriazole, and the added amount of benzotriazole is 0.1wt%-3wt%.
[0017] As a further solution of the present invention, in S3, the average particle size of the magnetic powder after surface treatment is 2.0±0.3 μm.
[0018] Phosphoric acid reacts with the surface of samarium iron nitrogen magnetic powder to generate phosphate and iron phosphate. These compounds form a dense passivation film on the surface of the magnetic powder, which can effectively prevent the magnetic powder from further oxidation. On the other hand, benzotriazole has good antioxidant properties and can form a protective layer on the surface of the magnetic powder to reduce the contact between the magnetic powder and oxygen, thereby reducing the oxidation rate. In addition, through the wet ball milling process, phosphoric acid and benzotriazole can continuously react with metals on the surface during friction to generate metal salt compounds, which play a lubricating and anti-wear role, thereby improving the mechanical properties of the magnetic powder. The two work together to improve the corrosion resistance, oxidation resistance and mechanical properties of the magnetic powder.
[0019] As a further embodiment of the present invention, in S4, the binder is composed of CPE (chlorinated polyethylene), calcium stearate, KH570 (coupling agent) and PE wax; Calculated based on the weight of magnetic powder, the added amount of CPE is 8wt%, the added amount of calcium stearate is 0.5wt%, the added amount of KH570 is 0.5wt%, and the added amount of PE (polyethylene) wax is 1wt%.
[0020] As a further solution of the present invention, in S4, the banburying temperature is 100° C.-120° C., and the banburying time is 1 hour.
[0021] As a further solution of the present invention, in S4, the size of the magnetic particles is 1 mm-5 mm.
[0022] As a further solution of the present invention, in S5, the temperature of the flat vulcanizing press for compression molding is 80°C-100°C, and the pressure is 10MPa-15MPa.
[0023] In the second aspect, a high-performance ultra-thin rare earth permanent magnet sheet is prepared by the above-mentioned preparation method, wherein the substrate of the rare earth permanent magnet sheet is samarium iron nitrogen (Sm2Fe 17 N x ) material, thickness is 0.2mm-0.4mm, surface magnetism>500Gs.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a method for preparing high-performance ultra-thin rare earth permanent magnet sheets. During the preparation process, rapid solidification and smelting is carried out by secondary feeding. By optimizing the process settings, the magnetic loss is effectively reduced while the surface magnetism of the sheet is improved. The rare earth permanent magnet sheets obtained by flat plate vulcanization pressing have a thickness of only 0.2mm-0.4mm, which effectively solves the problem that the calender in the prior art cannot be processed to less than 0.4mm. The sheet has strong corrosion resistance, is not easy to rust, has sufficient surface magnetism, and has strong magnetic properties. The preparation cost is low, and can meet the application requirements of specific scenarios.
[0025] 2. In the raw material ratio of the present invention, the loss of metal samarium during the smelting process can be compensated by compensating excess samarium, thereby ensuring that the alloy obtained by the final smelting is Sm2Fe 17 ; The subsequent process optimization reduced the amount of samarium volatilization, so that the excess samarium added was only 1wt%-10wt% excessive, while ensuring that the appearance of impurities was avoided, the amount of compensating samarium was effectively reduced, thereby reducing the cost of raw materials.
[0026] 3. During the smelting process, since iron has a high melting point, adding some samarium to the crucible can form a low melting point alloy with iron during the melting process, thereby effectively accelerating the melting of the iron raw material. By homogenizing the samarium-iron alloy sheet, it can further form a uniform Sm2Fe 17 phase, after hydrogen cracking and nitriding, Sm2Fe 17 N xMagnetic powder can effectively improve the magnetic properties of magnetic powder, thereby improving the magnetic properties of the final magnetic sheet. The surface magnetism of the magnetic sheet is higher than 500Gs, which solves the problem of low surface magnetism of thin magnets prepared by calendering in the prior art and meets the actual application needs.
[0027] 4. The mechanism of adding phosphoric acid and benzotriazole to the SmFeN magnetic powder for ball milling surface treatment mainly includes the formation of a passivation film by phosphoric acid through chemical reaction, the provision of anti-oxidation and lubrication protection by benzotriazole, and the acceleration of chemical reaction and homogenization treatment during the ball milling process. These factors work together to significantly improve the antioxidant, corrosion resistance and mechanical properties of the magnetic powder. Calcium stearate in the binder can significantly improve the fluidity of the magnetic powder particles, reduce the resistance during molding, and improve the remanence and consistency of the magnetic sheet. At the same time, as a lubricant, it reduces the friction between the magnetic powders, making the magnetic powders more uniform during the mixing process and avoiding agglomeration. The use of CPE and PE wax can significantly improve the bonding performance of the magnetic powder. As a thermoplastic elastomer, CPE has good flexibility and heat resistance and can maintain a stable bonding effect at high temperatures. At the same time, PE wax, as a lubricant and binder, can further improve the fluidity and mixing uniformity of the magnetic powder, thereby improving the mechanical properties of the final product; the coupling agent KH570 can form a chemical bond with the surface of the magnetic powder, enhance the surface density and bonding force of the magnetic powder, and thus improve its antioxidant properties.
[0028] 5. By using lower mixing temperature and flat vulcanization calendering temperature, the pressing and molding ability of magnetic powder can be effectively improved, thereby further reducing the loss of heavy magnetic properties during the processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention will be further described below in conjunction with the accompanying drawings.
[0030] Figure 1 The present invention is a process flow chart for preparing a high-performance ultra-thin rare earth permanent magnet sheet. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] See also Figure 1 A method for preparing a high-performance ultra-thin rare earth permanent magnet sheet comprises the following steps: The samarium raw material and the iron raw material are weighed according to a molar ratio of 2:17, and the input amount of the samarium raw material is increased, and the samarium raw material is 5wt% in excess; the iron raw material is selected as an iron rod with a purity of 99%, and the samarium raw material in the pre-stored silo is selected as metal samarium particles with a purity of 99.9%, and the particle size is 1mm-10mm; the raw materials are weighed according to the need to prepare 100 kg of samarium-iron alloy, of which the iron rod weighs 75.95 kg and the samarium particles weigh 25.25 kg, of which 25.25 kg includes an excess of 5wt% of samarium raw material; S1. Put the weighed iron rod and samarium particles accounting for 50wt% of the total amount of samarium raw materials into the crucible of the smelting furnace, and put the remaining samarium particles into the secondary feeding bin; evacuate to a vacuum degree of less than 10Pa, heat the raw materials in the crucible at a temperature of 1550°C to melt, then add the raw materials in the secondary feeding bin, continue to heat until completely melted, and continue to smelt for 40 minutes to obtain molten samarium-iron alloy steel liquid; the molten alloy passes through the tundish and the runner, and is poured onto a cooling roller with a rotation speed of 2r / min to form a continuous samarium-iron alloy strip, and falls onto the water-cooled plate below to obtain a samarium-iron alloy sheet; S2. After the samarium iron alloy sheet is naturally cooled to room temperature, it is placed in a vacuum heat treatment furnace and evacuated to 1×10 - 2 Pa, heat up to 1000℃, keep heat treatment for 5h, then stop heating; Cool to 260℃ and keep warm. In a vacuum environment, introduce hydrogen into the furnace. The absolute pressure of hydrogen is controlled at 0.08MPa. The hydrogenation time is 2h. After the hydrogen cracking is completed, the temperature is uniformly raised to 400°C at a rate of 10°C / min, nitrogen is filled to 0.5MPa, and the temperature is kept for reaction for 1 hour; then the temperature is uniformly raised to 530°C at a rate of 0.2°C / min, and the temperature is kept for reaction for 10 hours; the temperature is cooled to room temperature with the furnace to obtain nitrided magnetic powder with an average particle size of 20±2μm; S3, adding 1wt% phosphoric acid and 1wt% benzotriazole to the magnetic powder based on the weight of the magnetic powder, wet ball milling and drying to obtain surface treated magnetic powder with an average particle size of 2.0±0.3μm; S4, adding a binder to the surface treated magnetic powder, and kneading to obtain magnetic particles; Calculated based on the weight of the magnetic powder after surface treatment, 8wt% CPE, 0.5wt% calcium stearate, 0.5wt% KH570, and 1wt% PE wax were added, and the mixture was kneaded at 110°C for 1h to obtain magnetic particles with a size of 1-5mm. S5. The magnetic particles are pressed into shape using a flat vulcanizer at a temperature of 90° C. and a pressure of 13 MPa to obtain rare earth permanent magnet sheets with a thickness of 0.3 mm.
[0034] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0035] Example 2
[0036] A method for preparing a high-performance ultra-thin rare earth permanent magnet sheet, which differs from Example 1 in that the samarium raw material and the iron raw material are weighed according to a molar ratio of 2:17, and then the amount of samarium raw material input is increased, and the excess samarium raw material is 1wt%; the remaining steps and parameters are consistent with Example 1.
[0037] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0038] Example 3
[0039] A method for preparing a high-performance ultra-thin rare earth permanent magnet sheet, which differs from Example 1 in that the samarium raw material and the iron raw material are weighed according to a molar ratio of 2:17, and then the amount of samarium raw material input is increased, and the excess samarium raw material is 10wt%; the remaining steps and parameters are consistent with Example 1.
[0040] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0041] Example 4
[0042] A method for preparing a high-performance ultra-thin rare earth permanent magnet sheet is different from that of Example 1 in that, in S3, the amount of benzotriazole added is 3wt%; the remaining steps and parameters are consistent with those of Example 1.
[0043] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0044] Example 5
[0045] A method for preparing a high-performance ultra-thin rare earth permanent magnet sheet is different from that of Example 1 in that, in S3, the amount of benzotriazole added is 0.1wt%; the remaining steps and parameters are consistent with those of Example 1.
[0046] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0047] Example 6
[0048] A method for preparing a high-performance ultra-thin rare earth permanent magnet sheet, which differs from Example 1 in that, in S5, the pressing molding temperature of the flat vulcanizer is 80°C and the pressure is 15MPa, and the remaining steps and parameters are consistent with Example 1, and a rare earth permanent magnet sheet with a thickness of 0.4 mm is obtained by pressing.
[0049] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0050] Example 7
[0051] A method for preparing a high-performance ultra-thin rare earth permanent magnet sheet, which differs from Example 1 in that, in S5, the pressing molding temperature of the flat vulcanizer is 100°C and the pressure is 11 MPa, and the remaining steps and parameters are consistent with Example 1, and a rare earth permanent magnet sheet with a thickness of 0.2 mm is obtained by pressing.
[0052] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0053] Comparative Example 1 A method for preparing a rare earth permanent magnet sheet, which differs from Example 1 in that the samarium raw material and the iron raw material are weighed according to a molar ratio of 2:17, and then the amount of samarium raw material input is increased, and the samarium raw material is in excess of 20wt%; the remaining steps and parameters are consistent with Example 1.
[0054] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0055] Comparative Example 2 A method for preparing a rare earth permanent magnet sheet is different from that of Example 1 in that, in S3, the amount of benzotriazole added is 0wt%; the remaining steps and parameters are consistent with those of Example 1.
[0056] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0057] Comparative Example 3 A method for preparing a rare earth permanent magnet sheet is different from that of Example 1 in that, in S3, the amount of benzotriazole added is 5wt%; the remaining steps and parameters are consistent with those of Example 1.
[0058] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0059] Comparative Example 4 A method for preparing a rare earth permanent magnet sheet, which differs from Example 1 in that, in S5, the pressing molding temperature of the flat vulcanizer is 110°C and the pressure is 16MPa, and the remaining steps and parameters are consistent with Example 1, and a rare earth permanent magnet sheet with a thickness of 0.15mm is obtained by pressing.
[0060] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0061] Comparative Example 5 A method for preparing a rare earth permanent magnet sheet, which differs from Example 1 in that, in S1, an iron raw material and a samarium raw material are put into a crucible together without secondary feeding. S1 specifically comprises putting weighed iron rods and samarium particles into a crucible of a smelting furnace, evacuating the crucible to a vacuum degree of <10Pa, heating the raw materials in the crucible at a temperature of 1550°C to melt the raw materials, and then continuing to smelt for 40 minutes to obtain molten samarium-iron alloy steel liquid; the molten alloy is poured onto a cooling roller with a rotation speed of 2r / min through a tundish and a runner to form a continuous samarium-iron alloy strip, and falls onto a water-cooled plate below to obtain a samarium-iron alloy sheet; the remaining steps and parameters are consistent with Example 1.
[0062] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0063] Comparative Example 6 A method for preparing a rare earth permanent magnet sheet is different from that in Example 1 in that, in S2, the nitridation treatment is carried out by directly heating the temperature, specifically: after the hydrogen cracking is completed, the temperature is uniformly heated to 530°C at a rate of 10°C / min, nitrogen is filled to 0.5MPa, and after the reaction is kept warm for 10 hours, the temperature is cooled to room temperature with the furnace to obtain nitrided magnetic powder; the remaining steps and parameters are consistent with those in Example 1.
[0064] After magnetizing the magnetic sheet, test the surface magnetism; expose the magnetic sheet to an environment with a temperature of 85°C and a humidity of 85% for 10 hours, and observe the surface magnetism of the magnetic sheet at 1 cm 2 The number of rust spots on the surface of the magnetic sheet within the area, the test results are shown in Table 1.
[0065] The relevant process parameters and performance test results of Examples 1 to 7 and Comparative Examples 1 to 6 are shown in Table 1.
[0066] Table 1
[0067] As can be seen from Table 1, by comparing Examples 1 to 3 with Comparative Example 1, the amount of samarium is additionally added to the samarium raw material weighed according to the stoichiometric ratio of Sm:Fe=2:17. When the excess samarium is less, the rare earth content in the magnetic powder is lower. 17 After the phase, there are fewer non-magnetic phases, so it has a higher remanence, and after being made into magnetic sheets, it has a higher surface magnetism.
[0068] Comparing Example 1, Example 4, Example 5 with Comparative Example 2, Comparative Example 3, the more the amount of benzotriazole corrosion inhibitor is added within a certain range, the fewer rust spots the magnetic sheet has when undergoing corrosion resistance testing, and the better the corrosion resistance; when benzotriazole is added in excess, it may react with phosphoric acid, further affecting the formation and distribution of phosphates, and may accelerate the chemical reaction on the surface of the magnetic powder, changing the chemical properties of the surface of the magnetic powder, leading to irreversible loss of magnetic properties. Therefore, it is necessary to strictly control the amount of benzotriazole added to ensure the stable performance and reliability of the magnetic powder.
[0069] Comparing Example 1, Example 6, Example 7 and Comparative Example 4, the thickness of the magnetic sheet can be controlled by adjusting the temperature and pressure of the flat vulcanizing machine. When the thickness of the magnetic sheet is larger, the amount of magnetic phase contained is relatively more, and the surface magnetism is naturally relatively higher.
[0070] Comparing Example 1 and Comparative Example 5, under the same raw material amount conditions, when the samarium raw material is not fed twice and is melted and refined simultaneously with the iron raw material, the amount of samarium volatilization increases during the process; while the secondary feeding can effectively reduce the volatilization of Sm, and the Sm content is greatly increased, Sm2Fe 17 The phase is more uniform and the surface magnetism is larger.
[0071] Comparing Example 1 with Comparative Example 6, the stepwise heating method during the nitriding process can effectively control the rate and degree of the nitriding reaction, avoiding the problem of grain growth or uneven nitriding caused by excessive temperature. By cooling to room temperature with the furnace, stress concentration during the cooling process can be reduced, and the overall quality of the nitrided magnetic powder can be improved.
[0072] In summary, the magnetic particles in the present invention are pressed to 0.2mm-0.4mm by flat plate vulcanization, which can solve the problem that the calender in the prior art cannot process to less than 0.4mm; by adding 1wt%-10wt% excess samarium to the formula and homogenizing it, Sm2Fe 17 Alloy sheet, after hydrogen cracking and nitriding, obtain Sm2Fe 17 N x Magnetic powder can effectively improve the magnetic properties of magnetic powder, thereby improving the magnetic properties of the final magnetic sheet; the surface magnetism of the magnetic sheet is higher than 500Gs, which solves the problem of low surface magnetism of thin magnets prepared by calendering in the prior art and meets the needs of practical applications; through surface treatment after ball milling and adding 1wt% phosphoric acid + 1wt% corrosion inhibitor, the corrosion resistance of the magnetic powder is improved, thereby improving the corrosion resistance of the final magnetic sheet; by adding 8wt% CPE, 0.5wt% calcium stearate, 0.5wt% coupling agent, 1wt% PE wax and other organic binders, the internal mixing temperature and the flat vulcanization pressing temperature are low, which can effectively improve the pressing molding performance of the magnetic powder, thereby improving the pressing molding performance of the final magnetic sheet.
[0073] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-performance ultra-thin rare earth permanent magnet sheet, characterized in that: The following steps are involved: S1, melting all the iron raw materials and 45wt%-55wt% of the samarium raw materials under vacuum conditions, adding the remaining samarium, continuing to smelt, and pouring the obtained molten alloy onto a cooling roller to obtain a samarium-iron alloy sheet; S2, sequentially performing homogenization treatment, hydrogenation treatment and nitridation treatment on the samarium-iron alloy sheet to obtain nitrided magnetic powder; S3, adding phosphoric acid and corrosion inhibitor to the magnetic powder, wet ball milling, and drying to obtain surface treated magnetic powder; S4, adding a binder to the surface treated magnetic powder, and kneading to obtain magnetic particles; S5. The magnetic particles are pressed by a flat vulcanizing machine to obtain rare earth permanent magnet sheets.
2. The method for preparing a high-performance ultra-thin rare earth permanent magnet sheet according to claim 1, characterized in that: In S1, samarium raw material and iron raw material are weighed according to a molar ratio of 2:17, and 1wt%-10wt% of samarium raw material is added.
3. The method for preparing a high-performance ultra-thin rare earth permanent magnet sheet according to claim 1, characterized in that: In S1, all the iron raw materials and 50 wt% of the samarium raw materials are melted under vacuum conditions.
4. The method for preparing a high-performance ultra-thin rare earth permanent magnet sheet according to claim 1, characterized in that: In S1, the vacuum degree is <10Pa, the melting temperature is 1510°C-1580°C, and the melting time is 30min-50min.
5. The method for preparing a high-performance ultra-thin rare earth permanent magnet sheet according to claim 1, characterized in that: In S2, the homogenization treatment is to place the samarium iron alloy sheet into a heat treatment furnace, evacuate the vacuum and heat treat it at a temperature of 900°C-1100°C for 7.5h-8.5h; The hydrogenation treatment is to cool the homogenized samarium iron alloy sheet to 250°C-300°C and keep it warm, and then introduce hydrogen into the furnace under vacuum, with the absolute pressure of hydrogen controlled at 0.05MPa-0.15MPa, and the hydrogenation time is 2h; The nitriding treatment is to uniformly increase the temperature to 350°C-450°C at a rate of 10°C / min, fill with nitrogen to 0.5MPa, and keep the temperature for 1 hour; then uniformly increase the temperature to 500°C-550°C at a rate of 0.2°C / min, keep the temperature for 10 hours; and cool to room temperature with the furnace.
6. The method for preparing a high-performance ultra-thin rare earth permanent magnet sheet according to claim 1, characterized in that: In S3, the amount of phosphoric acid added is 1wt% based on the weight of the magnetic powder; The corrosion inhibitor is benzotriazole, and the added amount of benzotriazole is 0.1wt%-3wt%.
7. The method for preparing a high-performance ultra-thin rare earth permanent magnet sheet according to claim 1, characterized in that: In S4, the binder consists of CPE, calcium stearate, KH570, and PE wax; Calculated based on the weight of magnetic powder, the added amount of CPE is 8wt%, the added amount of calcium stearate is 0.5wt%, the added amount of KH570 is 0.5wt%, and the added amount of PE wax is 1wt%.
8. The method for preparing a high-performance ultra-thin rare earth permanent magnet sheet according to claim 1, characterized in that: In S4, the mixing temperature is 100°C-120°C, and the mixing time is 1 hour.
9. The method for preparing a high-performance ultra-thin rare earth permanent magnet sheet according to claim 1, characterized in that: In S5, the temperature of the flat vulcanizing press for pressing is 80°C-100°C and the pressure is 10MPa-15MPa.
10. A high-performance ultra-thin rare earth permanent magnet sheet, characterized in that: The rare earth permanent magnet sheet is prepared by the preparation method described in any one of claims 1 to 9, wherein the substrate of the rare earth permanent magnet sheet is samarium iron nitrogen material, the thickness is 0.2mm-0.4mm, and the surface magnetism is greater than 500Gs.
Citation Information
Patent Citations
Ultrathin flexible magnetic composite material and preparation method thereof
CN118213147A
Polyurethane composite material for 3D printing, and preparation method and application thereof
CN104910609A
A submicron anisotropic samarium iron nitrogen magnet powder and a method for preparing a hybrid bonded magnet therefrom
CN106312077A
Material for preparing high-temperature-resistant injection magnet and preparation method of high-temperature-resistant injection magnet
CN110648812A
Magnetic powder surface passivation treatment method
CN115483018A
Cited By
Rolled magnetic sheet and preparation method thereof
CN120545088A
A rolled magnetic sheet and its preparation method
CN120545088B